2008
DOI: 10.2134/agronj2007.0163
|View full text |Cite
|
Sign up to set email alerts
|

Economic Returns for Purchased or Contract‐Grazed Stockers on Marshall Annual Ryegrass

Abstract: A gronomy J our n al • Volume 10 0 , I s sue 5 • 2 0 0 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The linear decrease in ADG with increasing SR observed in this study is a common response that has been reported in numerous other studies (e.g., Derner, Hart, Smith, & Waggoner, ; Gunter, Beck, Hutchison, & Phillips, ; Inyang et al., ; Morgan et al., ; Phillips, Hart, Glimp, & Vontungeln, ; Sharrow et al., ; Stewart et al., ). Daily gains observed in this study were similar to those reported for annual ryegrass of 1.0 to 1.2 kg/d (Islam et al., ; Zaragoza‐Ramírez, Bransby, & Duffy, ). Sollenberger and Vanzant () reported that across a wide range of HM or forage allowance, a high proportion (60% to 90%) of variation in ADG is attributed to quantity.…”
Section: Discussionsupporting
confidence: 90%
“…The linear decrease in ADG with increasing SR observed in this study is a common response that has been reported in numerous other studies (e.g., Derner, Hart, Smith, & Waggoner, ; Gunter, Beck, Hutchison, & Phillips, ; Inyang et al., ; Morgan et al., ; Phillips, Hart, Glimp, & Vontungeln, ; Sharrow et al., ; Stewart et al., ). Daily gains observed in this study were similar to those reported for annual ryegrass of 1.0 to 1.2 kg/d (Islam et al., ; Zaragoza‐Ramírez, Bransby, & Duffy, ). Sollenberger and Vanzant () reported that across a wide range of HM or forage allowance, a high proportion (60% to 90%) of variation in ADG is attributed to quantity.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the SR eff ect, it appears that low herbage mass availability on annual ryegrass pastures, which leads to reduced forage allowance, may have limited animal performance at high SR in our study. Zaragoza-Ramírez et al (2008) reported ADG ranging from 1.0 to 1.2 kg for stocking rates ranging from 8 to 2 steers ha −1 grazing annual ryegrass, respectively.…”
Section: Animal Performancementioning
confidence: 99%
“…This difference can be attributed to lower N content and less aboveground biomass measured for ryegrass compared with other species. However, ryegrass is known to produce a dense, shallow root system (Curran et al, 2018) and has performed well in stocker cattle grazing situations in Alabama (Siri‐Prieto et al, 2007; Zaragoza‐Ramirez et al, 2008).…”
Section: Methodsmentioning
confidence: 99%